1978
DOI: 10.1139/v78-048
|View full text |Cite
|
Sign up to set email alerts
|

Thermolysis of Δ3-1,3,4-oxadiazolin-2-ones and 2-phenylimino-Δ3-1,3,4-oxadazolines derived from α,β-epoxyketones. An alternative method for the convers of α,β-epoxyketones to alkynones and alkynals

Abstract: Thermolyses in polar solvents, of Δ3-1,3,4-oxadiazolin-2-ones or 2-phenylimino-Δ3-1,3,4-oxadiazolines derived from α,β-epoxyketones, yields acetylenic carbonyl compounds. Good yields of acetylenic aldehydes and ketones are obtained for those cases in which the epoxide is ring fused. Extension to acyclic cases failed primarily due to predominance of a parallel decomposition pathway. The method complements the procedures developed by Eschenmoser and co-workers for the conversion of, α,β-epoxyketones into acetyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Thus, construction of the quaternary stereocenter was accomplished by using the diastereoselective Michael reaction as reported by dAngelo et al, [16] using a chiral enamine intermediate derived from 2ethylcyclohexanone (14) and (S)-1-phenethylamine to obtain the ketoester 15. After conversion of 15 into the epoxyketone 16 in a three-step sequence, Eschenmoser-Tanabe-type fragmentation was effected by conversion of 16 into a semicarbazone and subsequent oxidative fragmentation under the reaction conditions reported by Warkentin et al [17] to give aldehyde with a terminal acetylene. [18] The aldehyde was oxidized by Pinnick oxidation [19] to provide the carboxylic acid 17.…”
mentioning
confidence: 99%
“…Thus, construction of the quaternary stereocenter was accomplished by using the diastereoselective Michael reaction as reported by dAngelo et al, [16] using a chiral enamine intermediate derived from 2ethylcyclohexanone (14) and (S)-1-phenethylamine to obtain the ketoester 15. After conversion of 15 into the epoxyketone 16 in a three-step sequence, Eschenmoser-Tanabe-type fragmentation was effected by conversion of 16 into a semicarbazone and subsequent oxidative fragmentation under the reaction conditions reported by Warkentin et al [17] to give aldehyde with a terminal acetylene. [18] The aldehyde was oxidized by Pinnick oxidation [19] to provide the carboxylic acid 17.…”
mentioning
confidence: 99%
“…B. Fulton. stituent (X) at C2 (2). In systems lf and l g the two piece fragmentation pathway can account for all of the observations and there may be little competition from the three-piece pathway (5).…”
mentioning
confidence: 87%
“…[2]. Acetone-4-arylsemicarbazones, 3, were prepared from acetone semicarbazone by transamidation with the appropriate p-substituted aniline, following the method of Borsche (7).…”
Section: Synthesesmentioning
confidence: 99%
See 1 more Smart Citation
“…After extensive investigations we found that 6 reacted with semicarbazide, giving semicarbazone 7. According to Warkentin's procedure, 10) 7 was oxidized with lead tetraacetate to form the 1,3,4-oxadiazoline intermediate, which underwent an Eschenmoser-Tanabe-type fragmentation to afford 8 in 60% yield. After reduction of aldehyde 8 with sodium borohydride, Sonogashira coupling of 9 with 2-iodoaniline gave alkynylaniline 10.…”
Section: Synthesis Of Mersicarpinementioning
confidence: 99%